THE ORANGE TREE MOTIF AS PART OF THE “MYTH ABOUT ITALY” IN STENDHAL’S WRITINGS (Proceedings of Southern Federal University. Philology, 2012)
Kharlamova D.V.Keywords: orange tree motif, mythologization, the novel space, the autobiographic space, prerequisites.The article is devoted to the analysis of the orange tree motif in the tendency of the “mythologization” of Italy in Stendhal’s writings. Exploring the formation of this motif, the author of the article tries to distinguish the novel space from the autobiographical space. It helps to discover prerequisites of the “myth about Italy” conception.